Transparent ZnO Thin-Film Deposition by Spray Pyrolysis for High-Performance Metal-Oxide Field-Effect Transistors - Cho, Junhee; Hwang, Seongkwon; Ko, Doo-Hyun; Chung, Seungjun (MDPI, 2019)
Solution-based metal oxide semiconductors (MOSs) have emerged, with their potential for low-cost and low-temperature processability preserving their intrinsic properties of high optical transparency and high carrier mobility. In particular, MOS field-effect transistors (FETs) using the spray pyrolysis technique have drawn huge attention with the electrical performances compatible with those of vacuum-based FETs. However, further intensive investigations are still desirable, associated with the processing optimization and operational instabilities when compared to other methodologies for depositing thin-film semiconductors. Here, we demonstrate high-performing transparent ZnO FETs using the spray pyrolysis technique, exhibiting a field-effect mobility of similar to 14.7 cm(2) V-1 s(-1), an on/off ratio of similar to 10(9), and an SS of similar to 0.49 V/decade. We examine the optical and electrical characteristics of the prepared ZnO films formed by spray pyrolysis via various analysis techniques. The influence of spray process conditions was also studied for realizing high quality ZnO films. Furthermore, we measure and analyze time dependence of the threshold voltage (V-th) shifts and their recovery behaviors under prolonged positive and negative gate bias, which were expected to be attributed to defect creation and charge trapping at or near the interface between channel and insulator, respectively.
Keywords: ZINC-OXIDE; ELECTRICAL-PROPERTIES; FABRICATION; DEPENDENCE; COMPONENTS; GROWTH; DEVICE; TIME